Method for Changepoint Detection With Sample Size Accumulation During Radio Equipment Operation - Solomentsev, Oleksandr; Zaliskyi, Maksym; Herasymenko, Tetyana; Petrova, Yuliia (Electrical, Control and Communication Engineering, 2020)
The operation system determines the efficiency of the intended use of radio equipment. The operation system includes radio equipment, documentation, operational resources, personnel, processes, data processing algorithms, etc. The operation process is associated with conditions of priori uncertainty of models, parameters, external factors, etc. The main element for monitoring is technical condition of radio equipment. In a general case, this condition can deteriorate. The problems of technical condition deterioration analysis can be considered in terms of changepoint study. The present paper concentrates on the problem of synthesis and analysis of method for changepoint detection during radio equipment operation. The detection algorithm is constructed based on Neyman–Pearson criterion with sample size accumulation. During algorithm synthesis the thresholds were calculated according to Bellman’s approach. The problem of synthesis and analysis was solved by two methods: analytically and using statistical modelling. The efficiency measures for this algorithm are the probability of correct detection and mean time of decision making. The proposed algorithm has advantages in mean time of decision making compared with CUSUM detection method.